PENGARUH E-WOM, CITRA MEREK, HARGA, DAN KEPERCAYAAN TERHADAP MINAT BELANJA KONSUMEN E-COMMERCE - Suyono Saputra (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this study is to analyze factors that influence consumer purchase intention using e-commerce service in Batam city. Respondents who were the object of this study were 233 samples using judgemental sampling and processed using Partial Least Square (PLS) program. The results of this study indicate that e-WOM has no significant effect on consumer purchase intention, but e-WOM has significant effect on brand image and brand image has significant effect on purchase intention. Furthemore, price and trust also proven to have a significant effect on purchase intention. The conclusion of this study can be input for e-commerce service providers to pay attention to brand image enchancement programs through e-WOM intensity in various media channels, as well as paying attention to trust dan product selling prices to increase consumer purchase intention using e-commerce services in Batam city.